Energy-Consumption-Based Life Cycle Assessment of Additive-Manufactured Product with Different Types of Materials - Ülkir, Osman (Mdpi, 2023)
Additive manufacturing (AM) or 3D printing technology is one of the preferred methods to ensure sustainability in fabrication. In addition to providing continuity in sustainability, fabrication, and diversity, it aims to improve people's quality of life, develop the economy, and protect the environment and resources for future generations. In this study, the life cycle assessment (LCA) method was used to determine whether a product fabricated by the AM provides tangible benefits compared to traditional fabrication methodologies. LCA is an evaluation method that provides information on resource efficiency and waste generation, where the environmental impacts of a process can be calculated, measured, and reported throughout the entire life cycle, starting from the acquisition of raw materials, processing, fabrication, use, end of life, and disposal, according to ISO 14040/44 standards. This study examines the environmental impacts of the three most preferred filaments and resin materials in the AM for a 3D-printed product from the start, which consists of three stages. These stages are raw material extraction, manufacturing, and recycling. Filament material types are Acrylonitrile Butadiene Styrene (ABS), Polylactic Acid (PLA), Polyethylene Terephthalate (PETG), and Ultraviolet (UV) Resin. The fabrication process was carried out with Fused Deposition Modeling (FDM) and Stereolithography (SLA) techniques using a 3D printer. Environmental impacts for all identified steps were estimated over the life cycle using the energy consumption model. As a result of the LCA, it was seen that UV Resin was the most environmentally friendly material in the mid-point and end-point indicators. It has been determined that the ABS material also exhibits bad results on many indicators and is the least environmentally friendly. The results support those working with AM in comparing different materials' environmental impacts and choosing an environmentally friendly material.
Keywords: Additive Manufacturing; Life Cycle Assessment; Fdm; Sla; Energy Consumption; Fabrication; Sustainability